GRAIN-SIZE-SENSITIVE FLOW AND SHEAR-STRESS ENHANCEMENT AT THE BRITTLE-DUCTILE TRANSITION OF THE CONTINENTAL CRUST - Gueydan F.; Leroy Y.M.; Jolivet L. (My University, 2001)
Localized shear zones along low-angle normal faults have been identified in regions of extension at the brittle-ductile transition of the continental crust. The possibility of the strain localizing at a depth of 10 km is interpreted here as a consequence of an increase in the equivalent shear stress applied to the flow of the lower crust. This enhancement of the flow stress is seen as a prerequisite for the triggering of brittle deformation mechanisms leading to strain localization. The lower crust rheology used to examine this stress increase is strain-rate, temperature and grain-size dependent, due to the coupling of dislocation and diffusion creep. The model structure proposed consists of a top layer, the upper crust, gliding rigidly above a bottom layer, the lower crust, which deforms in simple shear. During a short time interval (1400 years), the equivalent shear stress is found to increase by a factor of up to 3 (67 MPa for anorthite and 17 MPa for quartz). For anorthite, this stress could explain the activation of a Mohr-Coulomb failure with a friction coefficient of 0.2, which is reasonable at the depth of 10 km. Dislocation creep is activated during a rapid change in the prescribed velocity, whereas diffusion creep dominates if the velocity is held constant, highlighting the importance of grain-size sensitivity for lower crustal rheology.
Keywords: METAMORPHIC CORE COMPLEXES; CONTINENTAL LOWER CRUST; GRAIN-SIZE-SENSITIVE RHEOLOGY; SHEAR ZONES; SHEAR STRESS ENHANCEMENT; BRITTLE DEFORMATION MECHANISMS; FINITE-ELEMENT METHOD